Sensitive electrochemical sensing platform based on Au nanoflower-integrated carbon fiber for detecting interleukin-6 in human serum - Madhu, Sekar; Han, Jang Hee; Jeong, Chang Wook; Choi, Jungil (Analytica Chimica Acta, 2023)
Prostate cancer (PCa) is the most prevalent cancer worldwide, with a high mortality rate. The early and accurate detection of PCa is critical in reducing mortality and saving lives. Timely diagnosis can improve the chances of successful treatment using advanced technologies. In recent years, nanomaterial-based electrochemical sensing strategies have been adopted in clinical diagnosis, as they allow sensitive early-biomarker detections to be converged with a cost-effective electronic readout system. Herein, we present a flexible electrochemical immunosensor platform for detecting interleukin-6 (IL-6) based on an Au-integrated flexible carbon fiber (Au/CF) electrode prepared via electrodeposition and chemically modiﬁed to capture IL-6 antibodies. Several techniques are used to analyze the prepared Au/CF composite electrodes to confirm their morphology, structure, and elemental composition. Under optimum conditions, the fabricated immunosensor exhibits a wide linear dynamic ranging from 1 fg/mL to 1 μg/mL and a low detection limit of 0.056 fg/mL, with a sensitivity of 62.17 μA/(fg mL−1). The proposed fiber-based immunosensor is used to quantify the concentration of IL-6 in serum samples from clinical PCa patients (T3b and T4 stages), and the results are validated using the commercial Meso Scale Diagnostics (MSD) V-Plex method. The acceptable results yielded by the proposed immunosensor indicate that it can serve as a new platform to realize highly sensitive and cost-effective diagnostic strategies for the early diagnosis of PCa.
Keywords: And flexible sensor; Cancer diagnosis; Cost effective; Electrochemical sensing; Flexible sensor; Gold nanostructures; Human serum; Interleukin6 (IL6); Prostate cancers; Sensing platforms; Antibodies; Biosensing Techniques; Carbon Fiber; Humans; Immunoassay; Interleukin-6; Male; And flexible sensor; Cancer diagnosis; Carbon fiber; Gold nanostructure; Immunosensor; Prostate cancer